2021
DOI: 10.1007/s40520-021-01991-z
|View full text |Cite
|
Sign up to set email alerts
|

Frailty but not sarcopenia nor malnutrition increases the risk of developing COVID-19 in older community-dwelling adults

Abstract: Background The identification of coronavirus disease 2019 (COVID-19) risk factors is requested to implement prevention strategies. Aim To explore the associations between the COVID-19 incidence and malnutrition, sarcopenia, and frailty, identified as potential risk factors in previous cross-sectional studies. Methods Malnutrition, sarcopenia, and frailty were assessed at the last available follow-up from the Sarcopenia and Physical Impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 66 publications
2
22
1
Order By: Relevance
“… 46 Another study carried out on 241 community‐dwelling older adults from the SarcoPhAge cohort, showed that frailty, assessed by Fried criteria, was associated with seven‐time higher risk of Sars‐CoV‐2 infection. 47 Here, we found an overall incidence of COVID‐19 positivity of 12.9%, which was roughly doubled in pre‐frail/frail subjects. However, independently by Sars‐CoV‐2 infection, we observed a significant worsening of frailty condition only in those subjects who were pre‐frail/frail before COVID‐19 outbreak.…”
Section: Discussionmentioning
confidence: 50%
“… 46 Another study carried out on 241 community‐dwelling older adults from the SarcoPhAge cohort, showed that frailty, assessed by Fried criteria, was associated with seven‐time higher risk of Sars‐CoV‐2 infection. 47 Here, we found an overall incidence of COVID‐19 positivity of 12.9%, which was roughly doubled in pre‐frail/frail subjects. However, independently by Sars‐CoV‐2 infection, we observed a significant worsening of frailty condition only in those subjects who were pre‐frail/frail before COVID‐19 outbreak.…”
Section: Discussionmentioning
confidence: 50%
“…Nutrition risk is highly prevalent among community-dwelling older adults in several countries [ 1 ], and a U.S. study showed that older age increased the risk of severe COVID-19 outcomes conferred by a history of malnutrition [ 36 ], although malnutrition per se may not increase the risk of contracting COVID-19 in older people [ 37 ]. Moreover, older adults are prone to developing frailty due to vulnerability to environmental stressors [ 9 , 10 ] such as a pandemic with mandated lockdown strategies that reduce physical contact with others and restrictions on shopping and travel.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia was measured in 3 studies [44,46,50] using strength, assistance with walking, rising from a chair, climbing stairs, and falls (SARC-F) questionnaire. In 2 studies [63,68], sarcopenia was measured via muscle strength with a hand-held handgrip dynamometer and body composition. The percentage of older adults with sarcopenia ranged from 33% [46] to 75% [44].…”
Section: Sarcopenia and Frailty Measurementsmentioning
confidence: 99%
“…The majority of the studies included hospitalized COVID-19 patients (n ¼ 33/39, 82%) [31e34,36,39e53,55e57,59e67,69], community dwelling elderly (n ¼ 2) [38,68], USA Medicare fee-for serviceeenrolled beneficiaries (n ¼ 1) [54], and long stay and care home residents (n ¼ 3) [35,37,58].…”
Section: Risk Of Development Of Severe Disease Among Older Covid-19 P...mentioning
confidence: 99%
See 1 more Smart Citation